VARIATIONS IN SPECTRUM OF COVID-19 CT FINDINGS AND ITS SEVERITY SCORING IN A TERTIARY CARE HOSPITAL OF BAHAWALPUR, SOUTHERN PUNJAB PAKISTAN - Khan, Sarah Nisar; Sarfraz, Lubna; mumtaz, Fariha; sidra, Khaula (Journal of Ayub Medical College Abbottabad, 2021)
Background: Recently the Coronavirus pandemic presented with different manifestations in different parts of the world, both on clinical examinations and on imaging. CT Scanning (CT Scan) chest is used for detailed evaluation of the different characteristic patterns determining the depth of disease. The study is aimed to assess the variations in spectrum of Covid-19 CT findings and relating severity (CT Severity Score) with the Clinical Symptoms in Bahawal Victoria Hospital, Bahawalpur. Methods: In this cross-sectional study, patients referred to radiology department from outdoor for COVID screening were included from 1st May to 30th June 2020. Mean age range of patients was calculated, while presenting complaints and co-morbidities were tabulated in frequencies and percentages after analysis. Severity of symptoms and CT findings were correlated with biochemical and haematological tests. Results: Patients’ age range from 25 to 85 years with 62% males and 38% females. Statistically no significant difference was observed in CTSS on gender basis. As sensitivity of RT PCR is about 70%, negative cases cannot be considered disease free and this is seen in this study as CT findings suggestive of COVID are seen in these patients. Using 40-point CT-SS, 11 patients had a score of >19 with severe diseases, while 14 patients had common disease with a score range of 11-18 and 35 patients had <10 score with mild or no symptoms. Conclusion: In this study, a spectrum of patchy ground glass opacities, bilateral peripheral predominantly lower lung consolidations were observed. Quantitative analysis of inflammatory process as occurring in lungs in Coronavirus Disease 2019, using 40-point CTSS scoring on Imaging could provide a timely and objective approach towards identifying patients requiring intensive care and hospitalisation. Keywords: COVID-19; Corona virus; CTSS (CT Severity Score); Ground-glass opacity